STUDI EVALUASI PEMOTONGAN HEWAN QURBAN DI KOTA BANDA ACEH DAN SEBAGIAN ACEH BESAR DARI ASPEK SANITASI DAN KESRAWAN Evalution Study of Qurban Slaughtering Animals in Banda Aceh City and Most Aceh Besar From Sanitation Aspect And Animal Welfare - tati maulidya; Razali Razali; Ismail Ismail; Rastina Rastina; Fakhrurrazi Fakhrurrazi; M Daud AK; Muhammad Hambal; Muttaqien Muttaqien (JURNAL ILMIAH MAHASISWA VETERINER, 2021)
This study aims to evaluate the slaughter of qurban animals in Banda Aceh City and some of Aceh Besar in 2017. This research was conducted in the form of data analysis from questionnaire results of qurban slaughtering animals. The data analyzed was data obtained from the results of questionnaires and observations about some aspects which classified into four categories, namely qurban animals health aspects, aspects of shelter and qurban animals slaughter equipment, the process of slaughtering qurban animals, and fourth was the aspect of cutting meat or carcass. The data were analyzed descriptively. The results showed that 83.28% of the health aspects of qurban animals in Banda Aceh city and some of Aceh Besar can be said very good. As many as 84.12% of the people in Banda Aceh city and some of Aceh Besar have done the shelter and qurban animal slaughtering equipment. 76.56% of the people in Banda Aceh city and some of Aceh Besar have done the slaughtering of qurban animals in accordance with slaughtering requirements, and 88.88% have done carcass or carcass handled properly. The conclusion stated that the slaughtering of qurban animals in Banda Aceh City and some of Aceh Besar in 2017 has fulfilled the aspect of sanitation and animal welfare